Microsurgical Experience with Pedicle-Sparing Transfacet Approach for Thoracic Disk Herniation - Çelik, Suat Erol; Samancı, Yavuz; Özkaya, Ferdi; Peker, Olgün (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Purpose Thoracic disk herniation (TDH) is relatively uncommon. The surgical approach differs from lumbar or cervical disk herniations because serious complications are associated with the posterior approach in TDH. Various different approaches have been tried for the surgical removal of TDH, but most of them are cumbersome surgeries such as thoracotomy or thoracoscopic or anterior approaches with or without instrumentation. The requirement for a simplified, familiar, and less morbid surgery has motivated some new approaches. A pedicle-sparing transfacet approach (PSTA) was first described in 1995, but to date no sufficient clinical series has been presented in the literature to report on its feasibility and applicability along with complication and morbidity rates. Our objective was to assess the feasibility of the PSTA under microscopic visualization in a cumulative clinical series.Methods Twenty-eight consecutive patients with no response to medical/physical treatment with and without motor weakness of their lower extremities underwent the surgery for TDH via the PSTA under microscopic visualization by a senior neurosurgeon. Preoperative and postoperative low extremity muscle strength, sensation, reflex status, and visual analog scores (VAS), Nurick grades, and complications were recorded. Postoperative MRI within 24 hours was performed. The median follow-up period was 33 months.Results The patients consisted of 16 men and 12 women. The disk levels ranged from T8 to T12–L1. All but one patient received one-level surgery. One patient was operated on two levels. A total of 21 patients had paracentral disk herniations; the other 7 had central disk herniations. Postoperative MRI showed satisfactory removal of disk herniation in all but one patient. There was no infection, wrong level surgery, or incidental durotomy. Median VAS levels significantly improved after the operation from 7.4 to 2.3. The Nuric grades decreased from 2.7 to 1.6 after surgery.Conclusions The microsurgical PSTA is a safe and feasible technique with a significantly shorter surgeon's learning curve. The approach offers a wide surgical window; moreover, it can by increased by tilting the surgical table allowing satisfactory decompression of TDH. After PSTA, segmental instrumentation is not required.
Keywords: microdiskectomy; thoracic disk herniation; thoracic spinal stenosis; posterior thoracic decompression; spinal cord